AN EMPIRICAL STUDY BUILD STOCK PORTFOLIO BY BUILDING CONSTRUCTION WITH CRUDE PETROLEUM AND NATURAL GAS SECTOR - WESLY MAILANDER SIAGIAN (LP2MTBM MAKARIOZ, 2021)
This paper aims to analyze the moving price in sub-sector building construction with crude petroleum and natural gas,selected the stock to build a portfolio with diversification method uses empirical data in both sub-sector. There are threemethodology using in this research: First, the author uses technical method and fundamental to analyse the stockperformance in sub-sector building construction with crude petroleum and natural gas. The technical analysis explained witha chart, while fundamental analysis with a company financial statements. Second, to build the actual portfolio, author usesdiversification method. Furthermore, author evaluating the return of a portfolio relative with Sharpe ratio, Treynor ratio andJensen’s alpha. Third, the portfolio combined by diversification method compared as different as the portfolio that using theconversion method and selected random or index market condition. Three primary results are drawn from this research thefollowing: First, the information moving price represent return rate sub-sector building construction higher than crudepetroleum and natural gas. The stock in sub-sector building construction is grow up in period 2014 to 2016, while anothersub-sector are grow down. Second, the diversification method will be obtain return rate higher. Last, return actual portfoliowhich is obtained with diversification method higher rather that conversion method, as well as to index market. This paper isthe examine how the portfolio in combined form the historical report previous period to result maximum return. In theaddition, the level risk of portfolio can be reference to the investor to build a portfolio that they wanted. This paper uses theempirical data in previous period to present a rational explanation estimated how much value of return to be obtained infuture time.